Rancang Bangun Fitur Pembayaran UKT Berbasis Dompet Digital DANA Menggunakan Metode Waterfall dan User Acceptance Testing - Novilya Musfira Bahri; Dzakwan Abbas; Muhammad Richie Hadiansyah (OKTAL : Jurnal Ilmu Komputer dan Sains, 2026)
This study aims to design and evaluate the integration of a Tuition Fee (UKT) payment feature using the DANA digital wallet into the Academic Information System (SIAKAD) of UIN Sumatera Utara to improve the efficiency of academic services. The system was developed using the Waterfall method. System evaluation was conducted through User Acceptance Testing (UAT) at the Alpha Testing stage using nine predefined test scenarios involving internal users. The testing results indicate that all nine test scenarios were successfully completed, achieving a 100% success rate. These results confirm that the system meets the specified requirements and user needs. The novelty of this study lies in the integration of a UKT payment feature using the DANA digital wallet directly into the SIAKAD of UIN Sumatera Utara, providing a practical and integrated digital payment alternative.